The implementation of the communicative approach and project-based learning model to improve maharah al-kalam at MI Nurul Falah - Yuliasari Yuliasari; Moch. Wahib Dariyadi; Laily Maziyah (Inovasi Kurikulum, 2025)
Arabic language learning in Madrasah Ibtidaiyah (Islamic elementary schools) plays a crucial role in developing speaking skills (maharah al-kalam), which serve as a key indicator of successful oral communication. However, preliminary observations at MI Nurul Falah, Bangka Regency, revealed that students’ speaking proficiency remains low, characterized by limited vocabulary, pronunciation difficulties, and low motivation caused by monotonous conventional teaching methods. To address these issues, this study implemented the communicative approach (al-madkhal al-ittisholi) and Project-Based Learning (PjBL) model. This research aimed to enhance Arabic-language skills among MI students. The study employed a two-cycle Classroom Action Research (CAR) design, utilizing observation, documentation, and performance assessments of speaking skills. The findings demonstrated significant improvement, with the mean score increasing from a pretest average of 58.27 to 75.36 in posttest in Cycle I, and further from a pretest of 80,51 to 90.62 in Cycle II. Authentic projects, such as developing dialogues (hiwar) and producing conversation videos, effectively fostered students’ active participation, collaboration, and self-confidence, while teachers functioned as facilitators supporting contextual learning. Thus, implementing PjBL within a communicative approach proved effective in improving Arabic-speaking skills at MI and can be recommended as an innovative strategy for Arabic language instruction in elementary madrasah settings.   Abstrak Pembelajaran bahasa Arab di Madrasah Ibtidaiyah (MI) berperan penting dalam membentuk keterampilan berbicara (maharah al-kalam) sebagai indikator utama keberhasilan komunikasi lisan. Namun, observasi awal di MI Nurul Falah Kabupaten Bangka menunjukkan bahwa keterampilan berbicara siswa masih rendah, ditandai dengan keterbatasan kosakata, kesulitan pelafalan, serta rendahnya motivasi akibat metode konvensional yang monoton. Untuk mengatasi hal tersebut, penelitian ini menerapkan pendekatan komunikatif (al-madkhal al-ittisholi) dan model Project-Based Learning (PjBL). Tujuan penelitian ini adalah untuk meningkatkan keterampilan berbicara bahasa Arab siswa MI. Penelitian dilakukan dengan metode Penelitian Tindakan Kelas (PTK) dua siklus menggunakan observasi, dokumentasi, serta penilaian kinerja berbicara. Hasil penelitian menunjukkan peningkatan signifikan dari rata-rata pretest 58,27 menjadi 75,36 pada nilai postest pada siklus I, dan dari rata-rata pretest 80,51 menjadi 90,62 pada nilai postest pada siklus II. Proyek nyata seperti penyusunan hiwar dan pembuatan video percakapan terbukti meningkatkan partisipasi aktif, kerja sama, serta kepercayaan diri siswa, sementara guru berperan sebagai fasilitator yang mendukung pembelajaran kontekstual. Dengan demikian, penerapan PjBL berbasis pendekatan komunikatif efektif dalam meningkatkan keterampilan berbicara bahasa Arab di MI dan dapat direkomendasikan sebagai strategi inovatif dalam pembelajaran bahasa Arab di madrasah dasar. Kata Kunci: Bahasa Arab; keterampilan berbicara; model PjBL; pendekatan komunikatif